Evaluasi Nilai CTDIvol Dan DLP Pada Pemeriksaan MSCT Abdomen Kontras Selama Periode Januari-Maret 2023 Di RSUP Dr Hasan Sadikin Bandung : Dengan Pendekatan ALADAIP - Anjelina Merry; Anak Agung Aris Diartama; I Kadek Sukadana (Jurnal Rumpun Ilmu Kesehatan, 2023)
Background: Abdominal MSCT examination is a type of radiodiagnostic examination that uses the MSCT device. Considering that the abdomen is close to organs that have radiosensitive properties such as the gonads and ovaries, it is necessary to monitor the radiation dose received so that it does not exceed the predetermined I-DRL value. The prevalence of contrast Abdominal MSCT examinations in the Radiodiagnostic Installation at Dr Hasan Sadikin Bandung Hospital was recorded during the last 3 months, there were 327 Contrast Abdominal MSCT examinations out of a total of 880 examinations with a percentage of contrast Abdominal MSCT examinations of 0.37%. This proves that contrast Abdominal MSCT examinations are often carried out but evaluation has never been carried out regarding the radiation dose received by the patient. Method: The type of research used in this research is descriptive quantitative with an observational approach by collecting data from patients with contrast Abdominal MSCT examinations during the period January-March 2023 with a sample of 128 patients. The local DRL value is calculated using the 2nd quart formula in the SPSS statistical application, then this local DRL value is compared with the I-DRL value determined by BAPETEN. Results: Calculation of the 50th percentile value of CTDIvol and DLP on 128 samples. The results show a CTDIvol value of 15.91 mGy and DLP of 740 mGy*cm. The DRL (50 percentile) values ​​based on gender are 13.71 mGy and 743 mGy*cm for men, and 17.74 mGy and 792 mGy*cm for women. Based on abdominal thickness, patients with a thickness of 10-19 cm have values ​​of 12.19 mGy and 587 mGy*cm, while patients with a thickness of 20-30 cm have values ​​of 22.57 mGy and 965 mGy*cm. For the most clinical cases (Ca Recti) the values ​​were 11.27 mGy and 586 mGy*cm. Conclusion: The 2nd quartile value (50 percentile) of CTDIvol and DLP received by patients during the Contrast Abdominal MSCT examination at the Radiodiagnostic Installation of RSUP Dr. Hasan Sadikin Bandung is in accordance with the standard values ​​set by BAPETEN/I-DRL 2021. However, special attention is needed for patients with an abdominal thickness of 20-30 cm, where the CTDIvol value exceeds the standards set by BAPETEN/I-DRL 2021.